14x^2-3xy+9y^2=71

2x+3y=9

I solve for x in the second equation and get x=-3y+9 /2 but when i plug it back in i am not sure how to square (-3y+9)/2 in the first equation?

Printable View

- November 15th 2008, 07:26 PMvbarnett326solving a system of nonlinear equations
14x^2-3xy+9y^2=71

2x+3y=9

I solve for x in the second equation and get x=-3y+9 /2 but when i plug it back in i am not sure how to square (-3y+9)/2 in the first equation? - November 15th 2008, 08:19 PMmr fantastic
- November 16th 2008, 11:16 AMvbarnett326
i don't understand how you got 63/2.

and also -3((-3y+9)/2))y equals (9y^2 -27y)/-6y?????? is that correct - November 16th 2008, 11:39 AMmr fantastic